Polychlorinated dioxins and dibenzofurans (PCDD/F), polybrominated dioxins and dibenzofurans (PBDD/F), polychlorinated biphenyls (PCB), polybrominated diphenyl ethers (PBDE), and per- and polyfluoroalkyl substances (PFAS) in German breast milk samples (LUPE 8) - Fromme, Hermann; Fuchs, Veronika; Albrecht, Michael; Aschenbrenner, Bettina; Röhl, Claudia; Janitzki, Nora; Herber-Jonat, Susanne; Wöckner, Mandy; Völkel, Wolfgang; Flemmer, Andreas W.; Schober, Wolfgang (The Science of the total environment, 2022)
Most organic pollutants (POP) are persistent in the environment, accumulate in fatty tissues, and so a transfer through the food chain is probably, thereby causing various health effects. We quantified PCDD/F, PBDD/F, PCB, PBDE, perfluorinated substances, and ADONA in breast milk samples collected in two German federal states and breast milk and blood samples from subjects additionally exposed to PFOA. The median (95th percentile) concentrations were 2.43 (6.58) pgWHO2005TEQ/g l.w. for PCDD/F, 2.45 (4.82) pgWHO2005TEQ/g l.w. for dioxin-like PCB (dl-PCB), and 0.62 (2.69) pgWHO2005TEQ/g l.w. for PBDD/F. The relative contributions of the median values of PCDD/F, dl-PCB, and PBDD/F to the total-TEQ were approximately 41%, 42%, and 11%, respectively. Nondioxin-like PCB (ndl-PCB) concentrations were clearly dominated by the higher chlorinated PCB congeners, with medians of 23.2 ng/g l.w. for PCB 153, 13.9 ng/g l.w. for PCB 138, and 13.0 ng/g l.w. for PCB 180. The sum of the 3 congeners (PCB 138, 153, and 180) were multiplied with 1.64 (total PCB) and showed a median of 82.16 ng/g l.w. and a 95th percentile of 173.3 ng/g l.w. Only PFOA and PFOS could be quantified in 29% and 17% of in total 180 samples with 95th percentiles of 53 ng/l and 33 ng/l, respectively. Milk samples (n = 13) from subjects living on PFOA contaminated sites showed higher levels between 33 and 854 ng/l PFOA (mean: 199 ng/l), whilst PFOS could be quantified only in three samples. The sum of 17 PBDE congeners showed medians (95th percentile) of 1737 pg/g l.w. (22,806 pg/g l.w.), with the highest medians of 422 pg/g l.w. for BDE 209 and 378 pg/g l.w. for BDE 153. Overall, our study confirms the declining contamination level in breast milk during the last decade, but points out the need to further reduce the environmental contamination with persistent substances and subsequently the exposure in childhood. [Display omitted] •We analyzed persistent substances in German breast milk samples.•Targets are PCDDs/Fs, PBDDs/Fs, PCBs, PBDE, and PFAS.•Concentration of the target compounds further declined.•Exposure of many substances partly exceed tolerable intake values.•A consistent reduction of environmental contamination is still needed.